The Form and Development of Jaran Kepang Dance in the Langen Budi Sedyo Utomo Association from 1996-2018 - Lukluil Maknun Al-izza; Eny Kusumastuti (Jurnal Seni Tari, 2023)
The Langen Budi Sedyo Utomo Association is located in Sombron Hamlet, Tlompakan Village, Tuntang District, Semarang Regency. The Langen Budi Sedyo Utomo Association in the course of the Jaran Kepang dance experienced development after the entry of the Songo dance in 1996. The problem that arose was the existence of external obstacles in the form of a lack of support from the people around regarding the views of dance art and maintenance of inventory of costumes, accompaniment or gamelan, and others. This study aims to analyze and describe the development of the form of the Jaran Kepang Dance at the Langen Budi Sedyo Utomo Association from 1996-2018. As well as the factors that influenced the development of the Jaran Kepang Dance form at the Langen Budi Sedyo Utomo Association from 1996-2018. The method used in this study is a qualitative research method that produces descriptive data. The research method used a qualitative method. Data collection techniques in this study used three techniques, namely observation techniques, interview techniques and documentation techniques. Interviews in this study were conducted 4 times with different informants. Based on the results of research conducted at the Langen Budi Sedyo Utomo community and the results of the discussion in chapter four, it can be concluded that the Jaran Kepang dance in the Langen Budi Sedyo Utomo community experienced development after the entry of the Songo dance, developments took place from year to year. From 1996-2013 the Jaran Kepang dance form in the Langen Budi Sedyo Utomo community still used movements that resembled Surakarta style dance movements, there was one dancer as the leader, then in 2013-2016, the Jaran Kepang dance form in the Langen Budi Sedyo Utomo community began to experience a variety of developments. movement and mining 1 Manggolo Yudho and 3 lead soldiers. In 2016-2018 the development of dance moves has been detailed because the movements have been updated by trainers who are more professional in their field. Developments can also be seen in costumes, makeup, and accompaniment.